People of the volcano Andean counterpoint in the Colca Valley of Peru - Cook, Noble David (Duke University Press, 2007)
Beneath the soaring condor -- Return of the Viracocha -- Crisis of the new order -- Constructing an "Andean utopia" -- "República de los Indios" : social and political structure -- Tribute and the domestic economy -- Extractive economy -- Indoctrination and resistance -- Crisis in the "república de los españoles" -- Epilogue: Andean counterpoint